RESEARCH AND CONTEXT FOR A THEORY OF MAORI SCHOOLING - Penetito, Wally (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2002)
ABSTRACT. This paper argues the case for introducing a Maori context for learning into mainstream schooling in New Zealand. Up to now, the system has only responded in minimal terms to such demands. The Education Amendment Bill currently before parliament and the National Administrative Guidelines have called for a new level of commitment from schools in relation to their consultation and delivery to Maori communities. This new commitment, it is argued, needs to begin with the philosophical debate to clarify what a 'Maori context' might mean. There is a need to move beyond the limitations of resistance to domination by Pakeha (New Zealanders of European origin) (Smith, 1992), and to engage in those practices that Maori perceive as being "worthwhile fighting for" (Hargreaves & Fullan, 1998). A specific theory of schooling is suggested. ÉLABORATION ET CONTEXTE D'UNE THÉORIE DE L'ENSEIGNEMENT MAORI RÉSUMÉ. Dans cet article, l'auteur défend l'idée de l'établissement d'un contexte d'apprentissage maori dans les programmes d'enseignement régulier en Nouvelle-Zélande. A ce jour, les autorités n'ont guère donné suite à cette proposition. Dans le projet de modification de la loi sur l'éducation dont est actuellement saisi le parlement néo-zélandais ainsi que dans les lignes directrices administratives nationales du pays, on préconise l'adoption par les écoles d'une politique renouvelée de consultation et d'intégration des collectivités maories. Avant d'élaborer cette nouvelle politique, il faut selon l'auteur tenir un débat philosophique sur ce que peut signifier un «contexte maori». Les Maoris doivent adopter une démarche qui dépasse la simple résistance à la domination des Pakehas, c'est-à-dire des Néo-zélandais d'origine européenne (Smith, 1992), et préserver les coutumes auxquelles ils attachent de l'importance (Hargreaves et Fullan, 1998). Une théorie d'enseignement spécifique est proposée.